Umbilical and fetal middle cerebral artery Doppler reference ranges in a twin population followed longitudinally from 24 to 38 weeks' gestation. (5th September 2014) - Mulcahy, C.; McAuliffe, F. M.; Breathnach, F.; Geary, M.; Daly, S.; Higgins, J.; Hunter, A.; Morrison, J.; Burke, G.; Higgins, S.; Dicker, P.; Mahony, R.; et al.
ABSTRACT Objective To construct monochorionic diamniotic (MCDA) and dichorionic diamniotic (DCDA) twin reference ranges for umbilical artery (UA) pulsatility index (PI), UA resistance index (RI), fetal middle cerebral artery (MCA) PI and peak systolic velocity (PSV) and cerebroplacental ratio (CPR) from 24 weeks' to 38 weeks' gestation and compare these with published normal values for singleton pregnancies. Methods This prospective multicenter cohort study included 1028 unselected twin pairs recruited over a 2‐year period. Participants with dichorionic twins underwent fortnightly ultrasound surveillance from 24 weeks' gestation, with monochorionic twins being followed every 2 weeks from 16 weeks until delivery. A total of 7536 fetal Doppler examinations in 618 twin pregnancies were included in the analysis, with reference ranges for MCDA and DCDA pregnancies constructed for each of the Doppler indices using multilevel modeling. Results UA‐PI and UA‐RI appear to be higher in twins than in singletons, and MCA‐PI and MCA‐PSV appear to be lower. The CPR also appears to be lower in twins than in singletons. Similar MCA indices were observed in MCDA and DCDA twins. Conclusion We have established longitudinal reference ranges for UA‐PI and UA‐RI, MCA‐PI and MCA‐PSV and CPR in twin pregnancies, which appear to differ from those in singleton pregnancies. The derived twin‐specific reference ranges may be more appropriate in the surveillance of these high‐risk pregnancies. Applying the singleton CPR cut‐off of ≤ 1.0 may lead to a large number of false‐positive diagnoses of cerebral redistribution in twin fetuses. Copyright © 2014 ISUOG. Published by John Wiley & Sons Ltd.